PENAFSIRAN AYAT-AYAT AL-QURâ€™AN TENTANG CAMBUK - Hayati, Ridha (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
This study focuses on the interpretation of the Qurâ€™an verses on whip according to two Acehnese commentators, namely Abdurrauf in the Quranic interpretation of Tarjum?n al-Mustaf?d and Hasbi in the Qurâ€™anic interpretation of an-Nur. Using Gadamer's hermeneutical approach, the result of this study shows that each of both interpretations of Abdurrauf and Hasbi is colored by the social conditions of the surrounding communities. An exegete can not be separated from previous understandings, both from his knowledge and the social conditions in which he lives. Abdurrauf uses the term â€œbeating or whackingâ€ to interprete the word jild, while Hasbi uses the term â€œwhipâ€ which each of those words was used in that period. In addition, according to Abdurrauf, the punishment for adulterers who were slaves was half of the free women, being whipped for 50 times and being exiled for half a year. As for Hasbi, she had to be whipped for 50 times without being exiled. Furthermore, Abdurrauf did not interpret the words ??'ifah and mu??anat into Malay, but absorbed directly from the language of the Qurâ€™an.